Multifunctional electrolyte additive for high power lithium metal batteries at ultra-low temperatures - Weili Zhang; Yang Lu; Qingqing Feng; Hao Wang; Guangyu Cheng; Hao Liu; Qingbin Cao; Zhenjun luo; Pan Zhou; Yingchun Xia; Wenhui Hou; Kun Zhao; et al. (Nature Communications)
Abstract Ultra-low-temperature lithium metal batteries face significant challenges, including sluggish ion transport and uncontrolled lithium dendrite formation, particularly at high power. An ideal electrolyte requires high carrier ion concentration, low viscosity, rapid de-solvation, and stable interfaces, but balancing these attributes remains a formidable task. Here, we design and synthesize a multifunctional additive, perfluoroalkylsulfonyl quaternary ammonium nitrate (PQA-NO3), which features both cationic (PQA+) and anionic (NO3 −) components. PQA+ reacts in situ with lithium metal to form an inorganic-rich solid-electrolyte interphase (SEI) that enhances Li+ transport through the SEI film. NO3 − creates an anion-rich, solvent-poor solvation structure, improving oxidation stability at the positive electrode/electrolyte interface and reducing Li+-solvent interactions. This allows ether-based electrolytes to achieve high voltage tolerance, increased ionic conductivity, and lower de-solvation energy barriers. The Li (40 µm)||NMC811 (3 mAh cm−2) coin cells with the developed electrolyte exhibited stable cycling at -60 °C and a 450 Wh kg−1 pouch cell retained 48.1% capacity at -85 °C, achieving a specific energy (except tabs and packing foil, same hereafter) of 171.8 Wh kg−1. Additionally, the pouch cell demonstrated a discharge rate of 3.0 C at -50 °C, reaching a specific power (except tabs and packing foil, same hereafter) of 938.5 W kg−1, indicating the electrolyte’s suitability for high-rate lithium metal batteries in extreme low-temperature environments.